Strategies to Improve the Performance of Tourism MSMEs through Entrepreneurial Competence, Orientation, and Motivation - Kiswadi Kiswadi; Sutianingsih Sutianingsih (Citakonsultindo, 2025)
This study aims to analyze the influence of entrepreneurial competence, entrepreneurial orientation, and entrepreneurial motivation on the performance of MSMEs in the tourism sector in Samiran Village, Selo, Boyolali. A quantitative approach was used in this study with the population of all MSMEs in the tourism sector in the location, totaling 45 MSMEs. Census techniques are applied in sampling, making the entire population the subject of the study. Data were collected through questionnaires and analyzed using multiple regression and t-tests. Before the regression analysis, validity, reliability, and classical assumptions tests (normality, multicollinearity, and heteroscedasticity) were performed. The results of the partial t-test showed that entrepreneurial competence, entrepreneurial orientation and entrepreneurial motivation had a positive and significant effect on the performance of MSMEs, respectively. The determination coefficient (R2) of 0.878 shows that 87.8% of the variation in MSME performance can be explained by these three independent variables.